Approximation Properties and q-Statistical Convergence of Stancu-Type Generalized Baskakov-Szász Operators. (20th January 2022) - Cai, Qing-Bo; Kilicman, Adem; Ayman Mursaleen, Mohammad
Abstract : In this article, we introduce Stancu-type modification of generalized Baskakov-Szász operators. We obtain recurrence relations to calculate moments for these new operators. We study several approximation properties and q -statistical approximation for these operators.